2012
DOI: 10.1155/2012/492608
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-Induced Cellular and Molecular Alteration of Immunocompetent Cells and Their Relationship with Chronic Inflammation and Carcinogenesis

Abstract: Asbestos causes lung fibrosis known as asbestosis as well as cancers such as malignant mesothelioma and lung cancer. Asbestos is a mineral silicate containing iron, magnesium, and calcium with a core of SiO2. The immunological effect of silica, SiO2, involves the dysregulation of autoimmunity because of the complications of autoimmune diseases found in silicosis. Asbestos can therefore cause alteration of immunocompetent cells to result in a decline of tumor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 70 publications
2
82
0
Order By: Relevance
“…Coding variants of TNFRSF13B have been implicated in common variable immunodeficiency, and the variant TNFR13BV was found to be up-regulated in both DEW and SP, and the expression was two-fold higher in SP than in DEW ( Table 1). This indicated that TNFR13BV may be involved in the increased and persistent immune response that occurred during silicosis development.It was reported that TNFs, interleukins, interferons, transforming growth factors and chemokines were essential for pulmonary fibrosis, and persistent up-regulation of related cytokines activates fibroblasts, and caused fibrosis of the extracellular matrix (1,13,22,23). In this study TNF, TNF superfamily member 4 isoform X1, interferon beta precursor, IL-6, atypical chemokine receptor 2 and the mutant IL-17F were all up-regulated in DEW and SP (Figures 1,2, Table 1).…”
mentioning
confidence: 99%
“…Coding variants of TNFRSF13B have been implicated in common variable immunodeficiency, and the variant TNFR13BV was found to be up-regulated in both DEW and SP, and the expression was two-fold higher in SP than in DEW ( Table 1). This indicated that TNFR13BV may be involved in the increased and persistent immune response that occurred during silicosis development.It was reported that TNFs, interleukins, interferons, transforming growth factors and chemokines were essential for pulmonary fibrosis, and persistent up-regulation of related cytokines activates fibroblasts, and caused fibrosis of the extracellular matrix (1,13,22,23). In this study TNF, TNF superfamily member 4 isoform X1, interferon beta precursor, IL-6, atypical chemokine receptor 2 and the mutant IL-17F were all up-regulated in DEW and SP (Figures 1,2, Table 1).…”
mentioning
confidence: 99%
“…In addition, inactivation of p16/ink4a, inactivation of tumor suppressor PTEN, and somatic mutations of BRCA 1-associated protein-1 (BAP1) were also reported in MPM cells (Kratzke et al 1995;Opitz et al 2008;Bott et al 2011;Testa et al 2011). We have focused on the immunological effects of asbestos; our studies have shown that asbestos fibers suppressed NK and CTL cell functions (Nishimura et al 2009a,b;Matsuzaki et al 2012;Kumagai-Takei et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Chronic inflammation is believed to play an important role in the etiology of this deadly disease. 4,22 Recently, we found that asbestos can prime and activate the NLRP3 inflammasome in mesothelial cells, 6 resulting in the release of the proinflammatory cytokines IL-1b and IL-18. IL-1b promotes EMT and cancer cell stemness in a number of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation has been implicated in the development and progression of MM, 2 and prevalently high circulating cytokines, which are incidentally associated with fibrosis (IL-6, platelet-derived growth factor, and IL-8), have been used as prognosticators of survival for patients with MM. 3,4 A recent massive parallel sequencing study of immortalized and primary mesothelial cells after asbestos exposure found that the most highly up-regulated genes after asbestos exposure belong to inflammatory networks, 5 further implicating inflammation as an important factor in the development of asbestosrelated diseases.…”
mentioning
confidence: 99%